2013
DOI: 10.1155/2013/908048
|View full text |Cite
|
Sign up to set email alerts
|

Treadmill Exercise Training Modulates Hepatic Cholesterol Metabolism and Circulating PCSK9 Concentration in High-Fat-Fed Mice

Abstract: Proprotein convertase subtilisin/kexin type 9 (PCSK9) is a novel biomarker of LDL clearance and a therapeutic target of cardiovascular disease. We examined the effects of aerobic exercise training in modulating PCSK9 abundance and hepatic sterol regulation in high-fat-fed C57BL/6 mice. Mice (n = 8) were assigned to a low-fat (LF), high-fat (HF), or an HF with exercise (HF + EX) group for 8 weeks. The HF + EX group was progressively trained 5 days/week on a motorized treadmill. The HF + EX group was protected a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 53 publications
3
11
0
Order By: Relevance
“…On the other hand, it was also reported that treadmill exercise resulted in increased LDL-R, PCSK9 and SREBP-2 mRNA expression in liver of high-fat-fed C57BL/6 mice. Reduction in hepatic cholesterol accumulation was mentioned as a main reason for higher hepatic LDL-R, PCSK9 transcript by treadmill exercise in high-fat-fed C57BL/6 mice (Wen et al 2013). It seems that higher hepatic cholesterol content in Chol-fed rats in our study is an underlying reason for lower hepatic LDL-R, PCSK9 transcript and consequently suppression of cholesterol uptake from plasma.…”
Section: Discussionsupporting
confidence: 49%
“…On the other hand, it was also reported that treadmill exercise resulted in increased LDL-R, PCSK9 and SREBP-2 mRNA expression in liver of high-fat-fed C57BL/6 mice. Reduction in hepatic cholesterol accumulation was mentioned as a main reason for higher hepatic LDL-R, PCSK9 transcript by treadmill exercise in high-fat-fed C57BL/6 mice (Wen et al 2013). It seems that higher hepatic cholesterol content in Chol-fed rats in our study is an underlying reason for lower hepatic LDL-R, PCSK9 transcript and consequently suppression of cholesterol uptake from plasma.…”
Section: Discussionsupporting
confidence: 49%
“…In rodents, treadmill exercise has been reported to increase liver ABCA1 mRNA levels in healthy rats [ 22 ] . Treadmill exercise also increased liver LDL-R, Pcsk9 and SREBP-2 mRNA in high-fat-fed C57BL/6 mice [ 23 ] while SR-B1 protein has been reported to be unchanged [ 24 ] . However, whether exercise training aff ects hepatic LDL-R, Pcsk9, Lrp1, and SR-B1 gene expression in Ovx animals is unknown.…”
mentioning
confidence: 93%
“…High-intensity resistance exercise increased non-HDL cholesterol in hamsters fed a hypercholesterolemic diet [41]. On the other hand, wild-type and LDL receptor knockout mice fed with an atherogenic diet had reduced LDL by exercise training [42,43]. Therefore, this effect seems to be related to the species background and/or to the presence of a high-fat diet.…”
Section: Discussionmentioning
confidence: 99%
“…However, in animal models, the effects on the LDL fraction are more variable; for instance, Von Duvillard et al [40] observed an increase in the LDLcholesterol fraction in pigs fed a hyperlipidemic diet and exercised. On the other hand, wild-type and LDL receptor knockout mice fed with an atherogenic diet had reduced LDL by exercise training [42,43]. On the other hand, wild-type and LDL receptor knockout mice fed with an atherogenic diet had reduced LDL by exercise training [42,43].…”
Section: Discussionmentioning
confidence: 99%